Bacillus megaterium Renuspore® as a potential probiotic for gut health and detoxification of unwanted dietary contaminants - Simon, Annie; Colom, Joan; Mazhar, Shahneela; Khokhlova, Ekaterina; Deaton, John; Rea, Kieran (Frontiers in Microbiology, 2023)
Exposure to diverse environmental pollutants and food contaminants are ever-increasing. The risks related to the bioaccumulation of such xenobiotics in the air and food chain haves exerted negative effects on human health such as inflammation, oxidative stress, DNA damage, gastrointestinal disorders and chronic diseases. The use of probiotics is considered an economical and versatile tool for the detoxification of hazardous chemicals that are persistent in the environment and food chain, and potentially for scavenging unwanted xenobiotics in the gut. . In this study, Bacillus megaterium MIT411 (Renuspore®) was characterized for general probiotic properties including antimicrobial activity, dietary metabolism, and antioxidant activity; and the capacity to detoxify several environmental contaminants that can be found in the food chain. In-silico studies revealed genes associated with carbohydrate, protein and lipid metabolism, xenobiotic chelation or degradation, and antioxidant properties. Bacillus megaterium MIT411 (Renuspore®) demonstrated high levels of total antioxidant activities, in addition to antimicrobial activity against Escherichia coli, Salmonella enterica, Staphylococcus aureus, and Campylobacter jejuni in-vitro. Additionally, Mmetabolic analysis demonstrated strong enzymatic activity with a high release of amino acids and beneficial short chain fatty acids (SCFAs). Moreover, Renuspore® effectively chelated the heavy metals mercury and lead without negatively impacting the beneficial minerals iron, magnesium or calcium;, and degraded the environmental contaminants nitrite, ammonia and 4-Chloro-2-nitrophenol. These findings suggest that Renuspore® may play a beneficial role in supporting gut health metabolism, and eliminating unwanted dietary contaminants.